To Fake or Not to Fake: Antecedents to Interview Faking, Warning Instructions, and Its Impact on Applicant Reactions - Law, Stephanie J.; Bourdage, Joshua; O’Neill, Thomas A. (Frontiers in Psychology, 2016)
In the present study, we examined the antecedents and processes that impact job interviewees’ decisions to engage in deceptive impression management (i.e. interview faking). Willingness and capacity to engage in faking were found to be the processes underlying the decision to use deceptive impression management in the interview. We also examined a personality antecedent to this behaviour, Honesty-Humility, which was negatively related to the use of deceptive impression management through increased willingness to engage in these behaviours. We also tested a possible intervention to reduce IM. In particular, we found that warnings against faking – specifically, an identification warning - reduced both the perceived capacity to engage in interview faking, and subsequent use of several faking behaviors. Moreover, this warning reduced faking without adversely impacting applicant reactions.